Consumption of Halal-Certified Products among Russian Consumers: an Empirical Investigation - Nariman Shamakov; Nur Asnawi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
This research study investigates the determinants of consumer intentions to buy products that have been halal certified in the context of the Muslim minority market, namely Russia. In this study, researchers sought to overcome gaps in the literature relating to consumer purchase intentions of halal certified products for Russian consumers. Russian consumers are having a large market but the majority are non-Muslim consumers so halal products must have Halal certification to ensure safety, quality and clarity for consumption. By utilizing the theory of planned behavior, this study aims to determine halal awareness, halal certification / logo, halal marketing, halal habits, halal knowledge, religious beliefs on Russian consumers' intention to buy halal certified products. It also seeks to identify the strongest factors also affecting intention to purchase halal food by Russian consumers. From a sample of 216 Russian consumers in the Tyumen Region, 204 questionnaires were found to be eligible for analysis. Data is collected through self-administered questionnaires. Multiple linear regression analysis is used to identify the relationships between the variables identified and to test the research hypotheses. The findings of this study indicate that the intention of Russian consumers to buy halal certified products is influenced by consumer knowledge about halal products and the encouragement of religious beliefs. Interestingly it was found that religious beliefs became the most dominant variable as a determinant of Russian consumer purchase intentions for halal-certified products.